2017
DOI: 10.3892/mmr.2017.7848
|View full text |Cite
|
Sign up to set email alerts
|

Torin2 enhances the radiosensitivity of MCF‑7 breast cancer cells by downregulating the mTOR signaling pathway and ATM phosphorylation

Abstract: Radiotherapy has an important role in the comprehensive treatment of breast cancer. However, the clinical outcome of adjuvant radiotherapy may be limited due to intrinsic radioresistance, it is necessary to explore efficient radiosensitization methods that improve the clinical outcome of patients undergoing radiotherapy. The present study aimed to investigate whether the novel mechanistic target of rapamycin (mTOR) inhibitor Torin2 enhances the radiosensitivity of MCF‑7 breast cancer cells. A Cell Counting Kit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(31 reference statements)
0
8
0
Order By: Relevance
“…The activation of these pathways protects cancer cells from the cytotoxic effects of radiation, ultimately leading to the development of radioresistance [ 9 ]. The activation of PI3K/AKT is highly involved in the development of radioresistance in several solid tumors including breast, lung, and prostate cancers [ 10 12 ]. Therefore, targeting these survival pathways in combination with radiotherapy may enhance therapeutic efficacy in breast cancer by attenuating cellular defense in response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of these pathways protects cancer cells from the cytotoxic effects of radiation, ultimately leading to the development of radioresistance [ 9 ]. The activation of PI3K/AKT is highly involved in the development of radioresistance in several solid tumors including breast, lung, and prostate cancers [ 10 12 ]. Therefore, targeting these survival pathways in combination with radiotherapy may enhance therapeutic efficacy in breast cancer by attenuating cellular defense in response to treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, investigators have also found that Torin2 was effectively cytotoxic against tumor cells and not cytotoxic to the non-malignant cells. Pre-treatment with Torin2 enhanced the efficacy of radiotherapy in breast cancer cells ( 49 ). Consistent with these findings, the results of the present study showed a significant effect of both Torin1 and Torin2 in suppressing cell growth and proliferation, with Torin2 demonstrating a higher degree of efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that torin2 also inhibited cellular activity against phosphatidylinositol 3-kinase-related kinase (PIKK) family kinases including ataxia telangiectasia-mutated kinase (ATM), ataxia telangiectasia-mutated, Rad3-related kinase (ATR) and DNA-PK, the inhibition of which sensitized cells to irradiation [45]. Luo et al showed that torin2 could enhance the radiosensitivity of breast cancer cells by downregulation the mTOR signaling and ATM phosphorylation [46]. Moreover, torin2 inhibited lionizing radiation-induced DNA damage repair [47].…”
Section: Discussionmentioning
confidence: 99%